Tumor protein 53‐induced nuclear protein 1 deficiency alters mouse gastrocnemius muscle function and bioenergetics in vivo. Issue 10 (23rd May 2019) - Warnez‐Soulie, Julie; Macia, Michael; Lac, Sophie; Pecchi, Emilie; Bernard, Monique; Bendahan, David; Bartoli, Marc; Carrier, Alice; Giannesini, Benoît
Abstract: Tumor protein 53‐induced nuclear protein 1 (TP53INP1) deficiency leads to oxidative stress‐associated obesity and insulin resistance. Although skeletal muscle has a predominant role in the development of metabolic syndrome, the bioenergetics and functional consequences of TP53INP1 deficiency upon this tissue remain undocumented. To clarify this issue, gastrocnemius muscle mechanical performance, energy metabolism, and anatomy were investigated in TP53INP1‐deficient and wild‐type mice using a multidisciplinary approach implementing noninvasive multimodal‐NMR techniques. TP53INP1 deficiency increased body adiposity but did not affect cytosolic oxidative stress, lipid content, and mitochondrial pool and capacity in myocyte. During a fatiguing bout of exercise, the in vivo oxidative ATP synthesis capacity was dramatically reduced in TP53INP1‐deficient mice despite ADP level (the main in vivo stimulator of mitochondrial respiration) did not differ between both genotypes. Moreover, TP53INP1 deficiency did not alter fatigue resistance but paradoxically increased the contractile force, whereas there were no differences for muscle fiber‐type distribution and calcium homeostasis between both genotypes. In addition, muscle proton efflux was decreased in TP53INP1‐deficient mice, thereby indicating a reduced blood supply. In conclusion, TP53INP1 plays a role in muscle function and bioenergetics through oxidative capacity impairment possibly as the consequence of abnormal mitochondrial respiration regulation and/or defective blood supply. Abstract : We report in mice that tumor protein 53‐induced nuclear protein 1 (TP53INP1) deficiency increases whole‐body fat accumulation and adiposity, but does not affect cytosolic oxidative stress, lipid content and mitochondrial pool and capacity in myocyte. In exercising gastrocnemius muscle in vivo, TP53INP1 deficiency reduces the oxidative ATP synthesis capacity and the proton efflux without altering the fatigue resistance, and paradoxically increases the contractile force. Beyond the demonstration that skeletal muscle is not involved in the development of metabolic syndrome induced by TP53INP1 deficiency, these data reveal that TP53INP1 plays a key role in the balance among muscle function and oxidative metabolism.